2013
DOI: 10.1136/jmedgenet-2013-101542
|View full text |Cite
|
Sign up to set email alerts
|

Ade novoX;8 translocation creates aPTK2-THOC2gene fusion withTHOC2expression knockdown in a patient with psychomotor retardation and congenital cerebellar hypoplasia

Abstract: We identified a balanced de novo translocation involving chromosomes Xq25 and 8q24 in an eight year-old girl with a non-progressive form of congenital ataxia, cognitive impairment and cerebellar hypoplasia. Breakpoint definition showed that the promoter of the Protein Tyrosine Kinase 2 (PTK2, also known as Focal Adhesion Kinase, FAK) gene on chromosome 8q24.3 is translocated 2 kb upstream of the THO complex subunit 2 (THOC2) gene on chromosome Xq25. PTK2 is a well-known non-receptor tyrosine kinase whereas THO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 32 publications
1
40
0
1
Order By: Relevance
“…THOC2 is in high abundance in the developing and mature human [10][11][12] and adult mouse brains. 6 We observed THOC2 in primary mouse hippocampal and cortical neurons and human cerebral cortex and hippocampus ( Figure S3). THOC2 function is critical for many living organisms as indicated by studies in yeast, roundworms, fruit flies, and vertebrates.…”
Section: Dysmorphismsmentioning
confidence: 89%
See 2 more Smart Citations
“…THOC2 is in high abundance in the developing and mature human [10][11][12] and adult mouse brains. 6 We observed THOC2 in primary mouse hippocampal and cortical neurons and human cerebral cortex and hippocampus ( Figure S3). THOC2 function is critical for many living organisms as indicated by studies in yeast, roundworms, fruit flies, and vertebrates.…”
Section: Dysmorphismsmentioning
confidence: 89%
“…6,13-17 THOC2 depletion has been shown to (1) interfere with mRNA export, chromosome alignment, mitotic progression, and genomic stability in humans 13,15 and (2) stimulate neurite outgrowth in primary rat hippocampal neurons. 6 Depletion of other TREX subunits also interferes with mRNA export, resulting in nuclear retention of mRNAs. 15,16,18 Mouse Thoc2, along with Thoc5, is required for epithelial stem cell self-renewal and differentiation.…”
Section: Dysmorphismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a patient with schizophrenia, the CCR apparently activated an alternative transcription mode, since the authors found 3 fusion transcripts [Eykelenboom et al, 2012]. While in 8 cases a fusion transcript was successfully demonstrated, other causes of the patient's phenotypes, such as haploinsufficiency of truncated genes, altered expression of unrelated genes, or additional CNVs, still have to be considered [Nothwang et al, 2001;Yue et al, 2005;Mansouri et al, 2006;Borsani et al, 2008;Backx et al, 2011;Eykelenboom et al, 2012;Kloosterman et al, 2012;Di Gregorio et Malli et al, 2014]. In 2 cases, regions of homology have been identified at the fusion points, such that for the other 8 cases NHEJ seems to be the most likely mechanism of fusion.…”
Section: Mechanisms Based On Disruption Of the Genomic Architecturementioning
confidence: 99%
“…Analyzing the data in this resource, Mitelman et al [2007] discovered that genome rearrangements in all forms of cancer had resulted in the formation of 358 gene fusions, which affected 337 genes. In the human germline, gene fusions were also found, albeit as extremely rare events resulting from copy number variations and complex chromosome rearrangements [Nothwang et al 2001;Yue et al, 2005;Mansouri et al, 2006;Borsani et al, 2008;Backx et al, 2011;Eykelenboom et al, 2012;Holt et al, 2012;Di Gregorio et al, 2013;Malli et al, 2014;Rippey et al, 2013;van Heesch et al, 2014;Bertelsen et al, 2015]. Hence, one could argue that gene fusions, resulting from chromosome rearrangements and occurring in both somatic cells and in the germline, would be such a type of abnormal chromosome constitution as hypothesized by Boveri [1914].…”
mentioning
confidence: 99%